Analyzing Execution Orderings on Hybrid Memory Consistency Models - Melo, Alba Cristina; Silva, Nilo Sergio Barros (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2000)
The behavior of Distributed Shared Memory Systems is dictated by the memory consistency model. To provide a better understanding on the semantics of the various consistency models, researchers have proposed formalisms to define them. Even with formal definitions, it is still difficult to say what kind of execution histories can be produced on a particular memory model. In this paper, we propose a visualization tool that generates the operations orderings that could have led to user-defined execution histories on different memory models. We also describe a prototype of our tool that analyses execution histories for two memory consistency models: Release Consistency and Scope Consistency. Some preliminary results are also presented.